Surgical Management of Paediatric Aphakia in the Absence of Sufficient Capsular Support - Evdoxia-Maria Karasavvidou; Craig Wilde; Anwar Zaman; Gavin Orr; Dharmalingam Kumudhan; Georgios D. Panos (Journal of Ophthalmology, 2021)
There are several available options for the demanding surgical correction of paediatric aphakia without sufficient capsular support. The literature suggests the implantation of a transscleral fixated posterior chamber-intraocular lens (PCIOL), an intrascleral fixated PCIOL, an iris-sutured intraocular lens (IOL), or an anterior chamber iris-claw IOL. We searched for reports on the management of paediatric aphakia in case of inadequate capsular support that delineated the diverse surgical approaches and their postoperative results. Analysis demonstrated that different complications can be encountered depending on IOL placement technique, such as suture rupture, IOL dislocation, secondary glaucoma, endophthalmitis, vitreous hemorrhage, and endothelial cell loss. However, it was shown that various IOL designs have similar visual outcomes. Taking into consideration the advantages and disadvantages of each surgical technique, ophthalmic surgeons can determine the safest and most efficient approach for paediatric aphakic patients.